2009
DOI: 10.1021/bi900708j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Strand-Specific Smooth Muscle α-Actin Enhancer Interaction by Purine-Rich Element Binding Protein B (Purβ)

Abstract: Expression of the smooth muscle α-actin gene in growth-activated vascular smooth muscle cells and stromal fibroblasts is negatively regulated by members of the Pur family of single-stranded DNA/RNA-binding proteins. In particular, Purα and Purβ are postulated to repress transcription by forming helix-destabilizing complexes with the sense strand of an asymmetric polypurine-polypyrimidine tract containing a canonical MCAT enhancer motif in the 5′ region of the gene. Herein, we establish the mechanism of Purβ bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 61 publications
7
36
0
Order By: Relevance
“…In support of this contention, the calculated IC50 values for the full-length protein and the core fragment were 1.3 and 0.5 nM, respectively. These values are consistent with previous estimates of the macroscopic binding affinity of Purβ for this sequence element based on quantitative band-shift and footprinting assays [17]. …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In support of this contention, the calculated IC50 values for the full-length protein and the core fragment were 1.3 and 0.5 nM, respectively. These values are consistent with previous estimates of the macroscopic binding affinity of Purβ for this sequence element based on quantitative band-shift and footprinting assays [17]. …”
Section: Resultssupporting
confidence: 92%
“…4B, the isolated core domain preferentially interacts with purine-rich sense (forward) strands of the PE32 and SPUR32 elements. With respect to the PE32 sequence, individual or combined mutation of the high affinity 3′ and 5′ binding sites and low affinity internal site [17], reduced the interaction of full-length NHis-Purβ and the core tryptic fragment in an analogous fashion (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified proteins, such as hnRNP A, hnRNP C1/C2, hnRNP D, VDAC 1 and 2, MSI-1, Pur-alpha, and Pur-beta, which are known to be involved in DDR22,25,34–40 (Table S1). In the present study, hnRNP C1/C2, Pur-alpha and Pur-beta, identified by Ingenuity Pathways Analysis, were further investigated due to their key roles in nucleic acid binding, regulation of transcription/translation, and association with telomeres and DDR 18,21,24,26,32…”
Section: Resultsmentioning
confidence: 99%
“…Further, hnRNP C1/C2 may play an important role in regulating p53 transcription in response to cytostatic drugs 22. Pur-alpha and Pur-beta are single-stranded DNA binding proteins, which form a heterodimeric complex23 and regulate DNA replication and transcription 24. Both Pur-alpha and Pur-beta have been linked with acute myelogenous leukemia and brain tumors 25,26.…”
Section: Introductionmentioning
confidence: 99%